What happens in the prefrontal cortex? Cognitive processing of novel and familiar stimuli in soccer: An exploratory fNIRS study - Schmaderer, L. F.; Meyer, M.; Reer, R.; Schumacher, N. (European Journal of Sport Science, 2023)
The importance of both general and sport-specific perceptual-cognitive abilities in soccer players has been investigated in several studies. Although these perceptual-cognitive skills could contribute significantly to soccer players` expertise, the underlying cortical mechanisms have not been clarified yet. Examining activity changes in the prefrontal cortex under different cognitive demands may help to better understand the underlying mechanisms of sports expertise. The aim of this study was to analyse the prefrontal activity of soccer experts during general and sport-specific cognitive tasks. For this purpose, 39 semi-professional soccer players performed four perceptual-cognitive tests, two of which assessed general cognition, the other two assessed sport-specific cognition. Since soccer is a movement-intensive sport, two tests were performed in motion. While performing cognitive tests, prefrontal activity was recorded using functional near-infrared spectroscopy (fNIRS) (NIRSport, NIRx Medical Technologies, USA). Differences of prefrontal activity in general and sport-specific cognitive tasks were analysed using paired t-tests. The results showed significant increases in prefrontal activity during general cognitive tests (novel stimuli) compared to sport-specific tests (familiar stimuli). The comparatively lower prefrontal activity change during sport-specific cognition might be due to learned automatisms of experts in this field. These results seem in line with previous findings on novel and automated cognition, "repetition suppression theory" and "neural efficiency theory". Furthermore, the different cortical processes could be caused by altered prefrontal structures of experts and might represent a decisive factor for expertise in team sports. However, further research is needed to clarify the prefrontal involvement on expertise in general and sport-specific cognition.